A PARALLEL CORPUS OF JAPANESE-RUSSIAN TRANSLATION OF A MANGA - Ninomiya , T. (Journal of Oriental Studies, 2024)
After the collapse of the Soviet Union, there was a strong influx of foreign culture into Russia. As part of the influx, Japanese manga entered the former Soviet Union, including Russia. The purpose of this paper is to present a parallel corpus of Japanese manga text Hadashi no Gen (Barefoot Gen), which was familiar to people in the former Soviet Union, and its Russian translation. The author has been studying the translation of Japanese literature and manga works into Russian from the standpoint of Descriptive translation studies, with the question, “How are Japanese literature, manga, and anime works translated into Russian?” As part of this research, the author has created a parallel corpus of Hadashi no Gen. The use of corpora is important to objectively clarify norms and laws of translation. This paper introduces the current state of Japanese manga translation studies and corpus-based translation studies, and then presents the parallel corpus of Hadashi no Gen. The author lays out three texts: the Japanese original text, the old Russian translation text, and the new Russian translation text. Finally, a case study using the corpus was presented. The present researcher showed how many times the name “Gen,” the main character of Hadashi no Gen, appears in the Japanese original text, the old Russian translation text, and the new Russian translation text, and what translation strategies were used. The results of the survey revealed that in the old Russian translation, the name Gen was removed due to page omissions, while in the new Russian translation, Gen which appeared as a vocative in the Japanese text was removed. In the case of the former translation, the name Gen was probably deleted for editorial reasons, but in the case of the latter, the name Gen was probably deleted to make the text more natural as Russian. This new edition would have been translated with the aim of providing a more readable text for Russians. Keywords: Parallel corpus, Manga, Hadashi no Gen, Japanese text, Russian text